Editor's Choice – Variation in Intact Abdominal Aortic Aneurysm Repair Outcomes by Country: Analysis of International Consortium of Vascular Registries 2010 – 2016. (July 2021) - Boyle, Jonathan R.; Mao, Jialin; Beck, Adam W.; Venermo, Maarit; Sedrakyan, Art; Behrendt, Christian-Alexander; Szeberin, Zoltan; Eldrup, Nikolaj; Schermerhorn, Marc; Beiles, Barry; Thomson, Ian; Cassar, Kevin; et al.
Abstract : Objective: Outcomes for intact abdominal aortic aneurysm (AAA) repair vary over time and by healthcare system, country, and surgeon. The aim of this study was to analyse peri-operative mortality for intact AAA repair in 11 countries over time and compare outcomes by gender, age, and geographical location. Methods: Prospective data on primary repair of intact AAA were collected from 11 countries through the International Consortium of Vascular Registries (ICVR) and analysed for two time periods, 2010 – 2013 and 2014 – 2016. The primary outcome was peri-operative mortality after endovascular aneurysm repair (EVAR) and open surgical repair (OSR). Multivariable logistic regression models were used to adjust for differences in patient characteristics. Results: A total of 103 715 patients were included. The percentage of patients undergoing EVAR increased from 63.6% to 71.2% ( p < .001) over the study period. This proportion varied by country from 35% in Hungary to 81% in the United States. Overall peri-operative mortality decreased from 2.1% to 1.6 % ( p < .001). Mortality also declined significantly over time for both OSR 4.2% to 3.6 % ( p = .002) and EVAR 1.0% to 0.7% ( p = .002). Mortality was significantly higher for female than male patients (3.0% vs. 1.6% p < .001). The percentage of patients > 80 years old undergoing AAA repair remained constant at 23.6% ( p = .91). Peri-operative mortality was higher for patients > 80 years than for those < 80 years old (2.7% vs. 1.6% p < .001). Forty-six per cent ( n = 275) of all EVAR deaths occurred in the over 80s. Conclusion: The proportion of AAA repairs performed using EVAR has increased over time. Peri-operative mortality continues to decline for both OSR and EVAR. Outcomes however were significantly worse for both women and those aged over 80, so efforts should be focused on these patient groups to further reduce elective AAA mortality rates.